REVITALIZING POLICY OF PEDESTRIAN BRIDGE WITHOUT ROOF IN SUDIRMAN JAKARTA: DILEMMA BETWEEN FUNCTION AND AESTHETICS - Avianto, Bhakti Nur; Utami, Dwi Nur (Universitas Nasional, 2021)
Purpose survey research is to answer for dilemma of public service facilities to assess how much benefits of revitalizing the pedestrian bridge without a roof in Sudirman Jakarta, given the problem for the pedestrian bridge cannot protect its users from the heat and rain. In addition, this building structure can be adjusted to the aesthetic advantages layout of the modern city. The quantitative survey method uses the Analytical Hierarchy Process model approach, which is a decision-making method by comparing the selection criteria in pairs and the pairwise comparison between the available options. The results showed that respondents expected the pedestrian bridge to return to its function of safety and comfort to be the top priority. In addition, there are also advantages in improving the aesthetics of urban planning which is the attraction of public facilities. Thus the decision as a reference that revitalization pedestrian bridge must prioritize its function to cross, not enjoy the city view, besides that, the pedestrian bridge without a roof needs to adjust to the season and weather in Jakarta which has an impact on public concerns about the dangers of bridge conditions for its users